Entre a imagem e a escrita: um estudo de abordagens psicogenéticas e a abordagem psicanalítica - Jeanne D'arc Silva de Carvalho (2004)
In Between image and writing, subject of this paper, I outstand the word between to the condition of a question. Would it be passage of image to writing, which must be understood according to an evolutive perspective? To answer this question I undertook a reading of psychogenetic approaches counterpointing them to psychoanalytic approach. The writings of Jean Piaget, Lev S. Vygotsky and Sigmund Freud allowed me to extract distinct notions of language and writing, clarifying what is named universal epistemological subject, subject of the speaking and subject of the unconscious. Instead of forcing a complement between those authors theories, the distinguishing points were discussed, extracting from their differences, fundamental contributions related to the proposed subject. It was possible to counterpoint the contributions of Psychoanalysis to the evolutive perspective of the writing, as far as the first trace, the scrawling and the sketches of human figure already have the statute of writing that only in a posteriori can be meant. From this discussion an unconscious knowledge was ascertained, which is different from the notion of knowledge and learning referred to the conscious universe. Pedagogical consequences could be ascertained. Taking the drawing as writing in a narrative way, the same as a production that approaches the enigmatic realness, a mistake resultant from the use and interpretation of this production, in an orthopedic or practice perspective is evidenced. It can be concluded that beside this evolutive perspective from image to writing, Psychoanalysis restart this discussion, concluding that the unconscious writes and in this case, the image is writing.